2002
DOI: 10.1104/pp.003566
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis ABI5 Subfamily Members Have Distinct DNA-Binding and Transcriptional Activities

Abstract: A small family of novel basic leucine zipper proteins that includes abscisic acid (ABA)-INSENSITIVE 5 (ABI5) binds to the promoter region of the lea class gene Dc3. The factors, referred to as AtDPBFs (Arabidopsis Dc3 promoter-binding factors), were isolated from an immature seed cDNA library. AtDPBFs bind to the embryo specification and ABA-responsive elements in the Dc3 promoter and are unique in that they can interact with cis-elements that do not contain the ACGT core sequence required for the binding of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
111
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(113 citation statements)
references
References 53 publications
(28 reference statements)
0
111
0
2
Order By: Relevance
“…4 C and M). ABI5 transcripts could be detected in floral tissues (24), which is coincident with the high accumulation of HY5 protein in floral tissues (25). Consistently, ABI5::GUS activity is barely detectable in hy5 floral tissues, in contrast to the strong GUS staining in the wild type (Fig.…”
Section: Abi5::gus Activity In Hy5 Is Reduced and Is Less Responsive mentioning
confidence: 63%
“…4 C and M). ABI5 transcripts could be detected in floral tissues (24), which is coincident with the high accumulation of HY5 protein in floral tissues (25). Consistently, ABI5::GUS activity is barely detectable in hy5 floral tissues, in contrast to the strong GUS staining in the wild type (Fig.…”
Section: Abi5::gus Activity In Hy5 Is Reduced and Is Less Responsive mentioning
confidence: 63%
“…ABI5 and ABI5-related bZIP transcription factors (AREBs (ABA responsive element-binding proteins), ABFs (ABRE binding Factors), and/or DPBFs (Dc3 promoter binding factors)), all possess similar domain architecture, consisting of a bZIP DNA-binding domain and four highly conserved regions, C1-C4 (25)(26)(27). The interaction between KEG and ABI5 occurs via the conserved C3 region of ABI5.…”
Section: Discussionmentioning
confidence: 99%
“…No interaction was observed with KEG , which lacks the ankyrin repeats. ABI5 contains a conserved bZIP DNA-binding domain and four highly conserved regions, C1-C4 (25,26) (Fig. 2C).…”
Section: Keg Interacts Directly With Abi5 In the Cytoplasm/tgn/ee-mentioning
confidence: 99%
“…A basic domain/Leu zipper transcription factor, ABI5, binds to ABRE (Kim et al, 2002), and another transcription factor, ABI3, binds to a sequence called a Sph/RY element (Suzuki et al, 1997;Ezcurra et al, 2000), which often is found adjacent to ABREs. Because both abi3 and abi5 confer ABA insensitivity and they behave as recessive mutations, ABI3 and ABI5 are positive regulators of the ABA response (Finkelstein et al, 2002).…”
Section: Ga-aba Interactionsmentioning
confidence: 99%